2023
DOI: 10.3389/fimmu.2023.1212770
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain-containing Protein 4 regulates innate inflammation via modulation of alternative splicing

Abstract: IntroductionBromodomain-containing Protein 4 (BRD4) is a transcriptional regulator which coordinates gene expression programs controlling cancer biology, inflammation, and fibrosis. In the context of airway viral infection, BRD4-specific inhibitors (BRD4i) block the release of pro-inflammatory cytokines and prevent downstream epithelial plasticity. Although the chromatin modifying functions of BRD4 in inducible gene expression have been extensively investigated, its roles in post-transcriptional regulation are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…We next explored the nature of interaction between IRF1 and BRD4 in the intrinsic innate response. BRD4 contains two highly conserved N-terminal bromodomains (BDs), BD1 and BD2, which mediate RSV-inducible interactions with ~100 proteins including transcription factors, chromatin regulators, spliceosome components, mediator proteins and polymerases ( 63 65 ); note in this analysis, IRF1 was not observed in the BRD4 CRC). We hypothesized that BRD4 BD serves to recruit coactivator complexes that function independently of its interaction with the PTEF-b complexes; complexes that interact with the COOH terminal BET domain ( 66 ).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…We next explored the nature of interaction between IRF1 and BRD4 in the intrinsic innate response. BRD4 contains two highly conserved N-terminal bromodomains (BDs), BD1 and BD2, which mediate RSV-inducible interactions with ~100 proteins including transcription factors, chromatin regulators, spliceosome components, mediator proteins and polymerases ( 63 65 ); note in this analysis, IRF1 was not observed in the BRD4 CRC). We hypothesized that BRD4 BD serves to recruit coactivator complexes that function independently of its interaction with the PTEF-b complexes; complexes that interact with the COOH terminal BET domain ( 66 ).…”
Section: Resultsmentioning
confidence: 92%
“…RSV infection increases ~100 proteins to bind the BRD4 complex ( 64 , 77 ). Through these associated proteins, BRD4 plays multiple functional roles in the coordinate genome innate response, including transcriptional elongation, stimulating enhancer remodeling, and mediating alternative mRNA splicing ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRD4 interactome analysis has uncovered approximately 100 proteins that are enriched in the BRD4 complex and responsive to respiratory syncytial virus (RSV)-infection and BRD4 inhibition [11], which is related to the BRD4's acetyl-lysine binding bromodomains. In addition, several studies also reported the role of BRD4 in regulating alternative splicing to control cell differentiation, heat shock response, and innate immune response [12][13][14].…”
Section: Introductionmentioning
confidence: 99%